Smart wireless sensor for quality product identification based on the NFC standard protocol and electromagnetic energy harvesting (2017)
This thesis presents an intelligent system for substance quality detection, uses an interdigitated electrode (IDT) as sensitive element and the Near Field Communication (NFC) protocol to establish a Wireless communication channel with a mobile device. As a electrical energy source, the sensor use energy harvesting tecnique from NFC electromagnetic couple. Aspects such as design of interdigitated electrode (IDT), the algorithms developed in an ultra low power microcontroller and the requirements to establish NFC communication are presented.